Effects of stroking parameters changes on time to exhaustion - Alberty, M.; Sidney, M.; Huot-Marchand, F.; Dekerle, J.; Gorce, P.; Lensel, G.; Pelayo, P. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study is to assess the technical modifications under constrained swimming during time to exhaustion tests (TTE). Ten swimmers performed a maximal 400-m front crawl test (V400), and 3 sets (S1, S2, S3) of 4 TTE at 95, 100, 105, and 110% of V400. In S1, swimmers had to sustain the velocities for the longest time as possible and the mean stroke rate (SR) was calculated (SRS1). In S2 and S3, velocities and SR were imposed (at SRS1 and SRs1-5%, respectively). TTE of S2 and S3 were shorter than those of S], During S3, an increase of the glide time was observed while propulsive time remained stable compared to S2. Swimming with a longer stroke length does not induce only a specific improvement of force production, but also the ability of the swimmers to adopt a more streamlined Position to reduce drag.